2011
DOI: 10.1055/s-0031-1275738
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate-Induced Visual Hallucinations

Abstract: An 11-year-old boy with attention deficit/hyperactivity disorder (ADHD) presented with visual hallucinations several years after starting methylphenidate (MPH). The hallucinations resolved upon discontinuation of the drug. Reports of toxic hallucinosis during treatment with MPH are rare. Although the pathogenetic mechanism is unclear, the occurrence of hallucinations may be explained by a chronic increase in synaptic dopamine. Clinicians should be aware of this possible rare adverse manifestation occurring at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…There are some reports of hallucinations associated with MPH (Gross-Tsur et al 2004;Porfirio et al 2011), and with acetaminophen (Servis and Connolly 1997;Carnovale et al 2013). However, there is no report on hallucinations with the combination of both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some reports of hallucinations associated with MPH (Gross-Tsur et al 2004;Porfirio et al 2011), and with acetaminophen (Servis and Connolly 1997;Carnovale et al 2013). However, there is no report on hallucinations with the combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…They result in few, generally mild, adverse effects, including decreased appetite, sleep disturbance, and abdominal pain (Wilens et al 2003). Tactile, visual, and auditory hallucinations have been reported in patients with ADHD during treatment with MPH at therapeutic doses (GrossTsur et al 2004;Porfirio et al 2011). These are described as rare, usually of acute onset, brief, and resolving within a few days after discontinuation of the medication (Ross 2006).…”
mentioning
confidence: 99%
“…It causes an increase in striatal dopamin signalling by holding dopamine more in synaptic cleft via dopamin transporter blockage and D1 receptor activation in postsynaptic neuron [2]. It has been reported that methylphenidate could rarely cause visual hallucinations, paranoid, somatic or reference delusions in with therapeutic doses [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, hallucinations emerged after taking the first and low dose medication has been thought an effect of idiosyncratic mechanism [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation